Multi-cell downlink coordinated beam forming algorithm based on fairness duality theory - Shi-wen HE; Yong-ming HUANG; Lv-xi YANG (Tongxin xuebao)
With the goal to optimize the multi-cell downlink beamforming based on the criterion of the worst-user rate maximization,the Lagrangian duality theory was first used to derive a virtual multi-cell uplink optimization problem that was dual to the primal multi-cell downlink beamforming optimization problem.Base on that,an iterative algorithm was developed to solve the virtual uplink problem by combining the methods of bisection search and geometric programming.Then,the primal multi-cell downlink coordinated beamforming optimization problem could be solved by converting the solution of the virtual uplink problem to the downlink.Simulation results demonstrate that,in contrast to the existing coordinated beamforming schemes,the proposed scheme achieves better performance in terms of both the worst-user rate and the rate per energy (RPE).